Sequestration and red cell deformability as determinants of hyperlactatemia in falciparum malaria - Ishioka, H; Ghose, A; Charunwatthana, P; Maude, R; Plewes, K; Kingston, H; Intharabut, B; Woodrow, C; Chotivanich, K; Sayeed, A; Hasan, M; Day, N; et al. (Oxford University Press, 2015)
Background: Hyperlactatemia is a strong predictor of mortality in severe falciparum malaria. Sequestered parasitized erythrocytes and reduced uninfected red blood cell deformability (RCD) compromise microcirculatory flow, leading to anaerobic glycolysis. Methods: In a cohort of patients with falciparum malaria hospitalized in Chittagong, Bangladesh, bulk RCD was measured using a laser diffraction technique, and parasite biomass was estimated from plasma concentrations of Plasmodium falciparum histidine-rich protein 2 (PfHRP2). A multiple linear regression model was constructed to examine their associations with plasma lactate concentrations. Results: A total of 286 patients with falciparum malaria were studied, of whom 224 had severe malaria, and 70 died. Hyperlactatemia (lactate level, ≥4 mmol/L) was present in 111 cases. RCD at shear stresses of 1.7 Pa and 30 Pa was reduced significantly in patients who died, compared with survivors, individuals with uncomplicated malaria, or healthy individuals (P < .05, for all comparisons). Multiple linear regression analysis showed that the plasma PfHRP2 level, parasitemia level, total bilirubin level, and RCD at a shear stress of 1.7 Pa were each independently correlated with plasma lactate concentrations (n = 278; R2 = 0.35). Conclusions: Sequestration of parasitized red blood cells and reduced RCD both contribute to decreased microcirculatory flow in severe disease.